Dynamics of protection in a shrinking economy: A peak into Zimbabwe’s refugee regime - Maviza, Gracsious; Nzima, Divane (University of the Western Cape Library Service, 2024)
Zimbabwe has consistently experienced an influx of refugees despite its shrinking economy. This places a heavy burden on the state to provide social protection to refugees. There are limited studies that focus on the dynamics of refugee protection in resource-constrained countries like Zimbabwe, often characterized as being only immigrant-sending countries. We use data from 12 in-depth interviews with key informants to explore how the prolonged socio-economic crisis has impacted the state’s ability to provide social protection to refugees in Zimbabwe. The study also explores the relationship between the state and other stakeholders in hosting refugees in Zimbabwe. The findings suggest that socio-economic challenges in a shrinking economy affect the protection outcomes of refugees regardless of the presence of a robust refugee regime in the country.